Evaluation of Serum CEA, CA19-9, CA72-4, CA125 and Ferritin as Diagnostic Markers and Factors of Clinical Parameters for Colorectal Cancer - Yanfeng Gao (Nature Portfolio, 2018)
Abstract Blood-based protein biomarkers have recently shown as simpler diagnostic modalities for colorectal cancer, while their association with clinical pathological characteristics is largely unknown. In this study, we not only examined the sensitivity and reliability of single/multiple serum markers for diagnosis, but also assessed their connection with pathological parameters from a total of 279 colorectal cancer patients. Our study shown that glycoprotein carcinoembryonic antigen (CEA) owns the highest sensitivity among single marker in the order of CEA > cancer antigen 72-4 (CA72-4) > cancer antigen 19-9 9 (CA19-9) > ferritin > cancer antigen 125 (CA125), while the most sensitive combined-markers for two to five were: CEA + CA72-4; CEA + CA72-4 + CA125; CEA + CA19-9 + CA72-4 + CA125; and CEA + CA19-9 + CA72-4 + CA125 + ferritin, respectively. We also demonstrated that patients who had positive preoperative serum CEA, CA19-9, or CA72-4 were more likely with lymph node invasion, positive CA125 were prone to have vascular invasion, and positive CEA or CA125 were correlated with perineural invasion. In addition, positive CA19-9, CA72-4, or CA125 was associated with poorly differentiated tumor, while CEA, CA19-9, CA72-4, CA125 levels were positively correlated with pathological tumor-node-metastasis stages. We here conclude that combined serum markers can be used to not only diagnose colorectal cancer, but also appraise the tumor status for guiding treatment, evaluation of curative effect, and prognosis of patients.